Educational Psychology and It's Role in Enhancing Sustainable Development in Iraq - Lect. Saad Abbas Oudah (Journal of College of Education, 2025)
This systematic review looks at the relationship between educational psychology and sustainable development in the context of Iraq's education system. The purpose of this paper is to explore the use of psychological theories in promoting sustainability education, to examine the obstacles Iraq faces in incorporating sustainability into its curriculum, and to assess the significance of innovative teaching approaches in overcoming these challenges. A comprehensive search of relevant literature published between 2010 and 2024 yielded 107 publications. The findings suggest that psychological factors such as intrinsic motivation and cognitive learning theories play an important role in improving the effectiveness of sustainability education. Despite these benefits, major obstacles to sustainability education have been discovered, such as curriculum gaps, resource constraints, and cultural issues. Innovative teaching practices, such as project-based learning and technology integration, were identified as effective ways to engage students and overcome infrastructural constraints. The evaluation finishes by arguing for curriculum change in Iraq, emphasizing the need of professional development for educators, and promoting context-specific techniques to address the region's unique issues. These findings are intended to help policymakers and educators in Iraq and other regions trying to improve sustainability teaching in their schools and universities.
Keywords: Educational psychology, sustainable development, Iraq , systematic review, learning, SDGs.